ANALYSIS OF CONSUMER PSYCHOLOGICAL TOWARDS PRICE DISCOUNTS: A CASE STUDY AT PAKUWON MALL YOGYAKARTA - Efendi, Lukman; Geta, Marinda (AIBPM Publisher, 2022)
The phenomenon that the price discounts has been altering consumer decisions in allocating revenue.This research aims to analyze how consumer behavior when there are discounted goods and to know the factor of consumer psychological in buying discounted goods.This research uses a quantitative approach and supported with qualitative approach.Methods of data collection in this research through questionnaires and interviews.The analysis technique used in this research is descriptive analysis techniques.The results of this research stated that most of consumers in Pakuwon Mall is more interested in shopping for discounted items.Consumers in the purchase of discounted goods with different motivations and most of them because of personal desires.This means that the consumers no longer considering their needs, but tend to consider price cuts attached to the goods.While the discount goods that are often purchased by consumers is clothing.Consumers are more interested in buying a discount on clothing because choice of clothing are always linked to the lifestyles and has become a habit.The results of this research are expected to be input for related parties to implement the right promotional mix to attract consumers to buy goods.Keywords: Consumer psychological, Discounts, Consumer behavior, Consumer decision, Choice.